Paradigm of the surroundings of historical monuments in Algeria: inventory and test of proposals - Hocine, Yasmine; Debache Benzagouta, Samira (Journal of Human Sciences, 2021)
Today's cities bear witness to disproportionate urban growth transforming their urban, architectural, historical and cultural morphology, strongly altering the historical monuments inherited from previous civilisations. Indeed, these vestiges of the past are isolated or buried in their surrounding space, which is detrimental to this heritage and urban ensemble at the same time. Today, more than ever, the question concerns the fate of the monument-approach duo, which can in no way be treated separately and requires an in-depth study and action strategies. In this article, we will look at the importance of the surroundings in the enhancement of heritage. The strongly altered image of the latter in Algeria as well as multisectoral proposals for a better understanding of the surroundings of historic monuments will also be presented. The objective is to propose a new reading and delimitation grid of the surroundings, new principles, and the revision of the legislation in force.